Características morfométricas e rendimento corporal do suruvi Steindachneridion scriptum agrupados por sexo - Maghelly, Otavio Rechsteiner; Huergo, Giuliano Maia; Zaniboni Filho, Evoy; Enke, Dariane Beatriz Schoffen [UNESP] (Inst Pesca, 2014)
The body shape, body yields and morphometric ratios is important for species characterization and evaluation of their productive potential. The aim of this study was to determine the morphometric reasons, the body yields and correlations for male and female suruvi, Steindachneridion scriptum. Was analyzed 30 males and 30 females, and length and weight measurements were made. Was calculated carcass yields and morphometric relationships. The design was complete randomized. Data were subjected to analysis of normality; variance and means were compared by t test and Mann Whitney test. The average total weight of males was 1,583.50 +/- 263.79 g, while the total weight of females was 1,606.66 +/- 185.34 g. The total lengths were 53.42 +/- 2.64 cm for males and 53.35 +/- 1.98 cm for females. Average total weight and total lengths was similar between the sexes (P>0.05). Dress out yields of 65.54 +/- 1.36% (males) and 65.71 +/- 1.20% (females) and edible portions of 41.99 +/- 1.66% (males) and 41.93 +/- 2.05% (females) did not differ significantly between the sexes (P>0.05). The percentage of head relative to the total weight was significantly higher in males (17.67 +/- 1.24%) than in females (16.90 +/- 0.85%). The weight of the viscera such as the percentage relative to the total weight was significantly higher in females. The species has no body yields and morphometric characteristics limitations for commercial production.

A determinação do formato do corpo, razões morfométricas e rendimento corporal é importante para a caracterização das espécies e avaliação do seu potencial produtivo. O objetivo do estudo foi determinar as razões morfométricas, os rendimentos corporais e suas correlações para machos e fêmeas de suruvi, Steindachneridion scriptum. Foram analisados 30 machos e 30 fêmeas, dos quais foram tomadas medidas de comprimento, peso e calculados os rendimentos de carcaça e relações morfométricas. O delineamento foi inteiramente casualizado. Os dados foram submetidos à análise de normalidade, variância e as médias comparadas pelos testes t e Mann Whitney. A média do peso total dos machos foi de 1.583,50 ± 263,79 g, enquanto a do peso total das fêmeas foi de 1.606,66 ± 185,34 g. Os comprimentos totais foram de 53,42 ± 2,64 cm para os machos e 53,35 ± 1,98 cm para as fêmeas. Peso total e comprimento total foram semelhantes entre os sexos (P>0,05). Os rendimentos de tronco limpo de 65,54 ± 1,36% (machos) e 65,71 ± 1,20% (fêmeas) e partes comestíveis de 41,99 ± 1,66% (machos) e 41,93 ± 2,05% (fêmeas), não diferiram significativamente entre os sexos (P>0,05). A porcentagem de cabeça em relação ao peso total foi significativamente maior nos machos (17,67 ± 1,24%) do que nas fêmeas (16,90 ± 0,85%). O peso das vísceras e a porcentagem destas em relação ao peso total foram significativamente maiores nas fêmeas. A espécie não apresenta limitações quanto aos rendimentos corporais e às características morfométricas para produção comercial.
Morphometric characteristics and carcass yields of suruvi Steindachneridion scriptum arranged by sex
Keywords: Processing; Carcass; Filleting; Morphometric parameters; Processamento; Carcaça; Filetagem; Morfometria